Penerapan Iptek Dalam Peningkatkan Kapasitas Produksi Keripik Pisang Pada UMKM Safnur Di Desa Lengkong Kecamatan Rakit Kabupaten Banjarnegara - M. Aris Pujiyanto; Dwi Putrianan N Kinding; Muhamad Solekan; Fitri Adi Setyorini (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
The application of appropriate technology has an important role in increasing the production capacity and product quality of MSMEs. This service aims to increase the production capacity of Safnur MSMEs in Lengkong Village, Rakit District, Banjarnegara Regency through the implementation of a spinner tool. The results of the service showed that the use of the spinner tool succeeded in increasing production capacity from 10 kg to 15 kg per day, as well as reducing drying time by up to 66%. In addition, the quality of banana chips products also increases significantly with lower oil content, resulting in products that are crisper and last longer. The training and assistance provided to Safnur MSME workers ensures optimal use of spinner tools, increasing production efficiency and consistency. The implications of the results of this service are not only increasing income and business sustainability of Safnur MSMEs but also opening up new job opportunities for the surrounding community. This success can be used as a model for the development of other MSMEs in the area. Recommendations are given for the continued use of spinner tools and the development of MSMEs through appropriate technology support, ongoing training, and collaboration with the government and related institutions.